Re-characterization of an extrachromosomal circular plasmid in the pathogenic Leptospira interrogans serovar Lai strain 56601 - Huang, Lili; Zhu, Weinan; He, Ping; Zhang, Yan; Zhuang, Xuran; Zhao, Guoping; Guo, Xiaokui; Qin, Jinhong; Zhu, Yongzhang (Acta biochimica et biophysica Sinica, 2014)
In China, Leptospira interrogans serovar Lai strain 56601 （str.56601） is one of main pathogenic strains that cause severe leptospirosis in both human and animals. The genome of this organism was completely sequenced in 2003. However, in 2011, we identified and corrected some assembly errors in the str.56601 genome due to the repeat sequences widely distributed in the Leptospira genome. In this study, we re-analyzed the previously reported mobile, phage-related genomic island in the chromosome and rectified detailed sequence information in both the plasmid and chromosome using various experimental methods. The presence of a separate circular extrachromosomal plasmid was also confirmed, and its location in the genomi~ region was determined relative to the genomic island reported in L. interrogans serovar Lai by a combination of pulsed-field gel electrophoresis -based and plasmid extraction-based Southern blot analysis. This report confirmed that the sep arate extrachromosomal circular plasmid is not integrated into the chromosome of. interrogans str.56601 and markedly improved our understanding of the genomic organization, evolution, and pathogenesis of L. interrogans. In particular, characterization of this extrachromosomal cir cular plasmid will contribute to the development of genetic manipulation systems in pathogenic Leptospira species.